University Students’ Engagement with Feedback in a Quiz Platform: A Case Study of Quizizz - Le, Mai Thi Truc; Tran, Khue Van (Journal of University Teaching and Learning Practice, 2024)
Students’ engagement with feedback is vital for the learning process. It is widely acknowledged that technology can enhance students’ engagement with feedback. However, research on technology-generated feedback tools emphasises that different technologies have varying impacts on students’ engagement. Recently, there has been a dearth of research shedding light on students’ engagement with feedback from quiz platforms. This mixed-methods study aims to examine the extent to which and how students engage with feedback on the Quizizz platform, drawing from Fredrick et al.’s (2004) framework of student engagement, including affective engagement, behavioural engagement, and cognitive engagement. Data were collected from a questionnaire with 294 respondents who were learning English as a foreign language at a private university in Vietnam and three focus group interviews with 15 participants. The findings indicate that participants moderately engaged with feedback from the quiz platform, and these engagements were quite complex. Moreover, data from the interviews revealed aspects of the quiz platform that can enhance students’ engagement with feedback. Additionally, an Exploration Factor Analysis was conducted to explore the structure of the questionnaire measuring students’ engagement with feedback, which confirms the usefulness of the framework in measuring students’ engagement with feedback from an interactive platform. The implications for using a quiz platform regarding students’ feedback literacy were discussed.